2013
DOI: 10.1080/14786419.2013.856904
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian brown propolis elicits antileishmanial effect against promastigote and amastigote forms ofLeishmania amazonensis

Abstract: Propolis is a complex matrix of chemical constituents extracted from plants and produced by bees which is used in folk medicine due to its several pharmacological properties. Its chemical composition varies according to the region where it is produced. This work has studied the antileishmanial activity and cytotoxicity of brown propolis (BP) originating from the semi-arid region of Piauí, Brazil. The BP showed significant inhibition of the Leishmania amazonensis promastigotes growth as well as being effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The fact that the bees from hives located along the northeastern coast of Brazil visited D. ecastaphyllum to collect resin on the plant's surface to produce red propolis has been previously reported 12,28 . Although there is a wide range of studies related to the leishmanicidal activity of different types of propolis in different regions of Brazil and the world 20,23,[33][34][35][36][37][38][39][40] , regarding red propolis, especially the red propolis from Sergipe, there is little information available. In this way, it was evaluated for the first time the effects of different concentrations of hydroethanolic extracts obtained from red propolis from Sergipe and of the inner bark of D. ecastaphyllum on the growth of promastigotes of L. amazonensis and L. chagasi.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the bees from hives located along the northeastern coast of Brazil visited D. ecastaphyllum to collect resin on the plant's surface to produce red propolis has been previously reported 12,28 . Although there is a wide range of studies related to the leishmanicidal activity of different types of propolis in different regions of Brazil and the world 20,23,[33][34][35][36][37][38][39][40] , regarding red propolis, especially the red propolis from Sergipe, there is little information available. In this way, it was evaluated for the first time the effects of different concentrations of hydroethanolic extracts obtained from red propolis from Sergipe and of the inner bark of D. ecastaphyllum on the growth of promastigotes of L. amazonensis and L. chagasi.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, lupeol-rich extracts and fractions has demonstrated a marked antileishmanial effect and low cytotoxicity. A previous study reported that the hexanic fraction of Brazilian brown propolis possess lupeol-high content and a marked antileishmanial activity against promastigote and amastigote forms of L. amazonensis, as well as low cytotoxicity when compared with the ethanol extract (Santana et al 2014).…”
Section: Resultsmentioning
confidence: 97%
“…Santana et al . () reported antileishmanial activity of brown propolis from the semi‐arid region of Brazil. This propolis showed growth inhibition of L. amazonensis promastigotes with IC 50 values ranging from 4·96 to 36·95 μ g ml −1 , depending on the extraction solvent of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Its botanical source was the Asteraceae Baccharis dracunculifolia, and the chemical composition includes phenolic compounds, diterpenes, triterpenes and essential oils (da Silva et al 2013). Santana et al (2014) reported antileishmanial activity of brown propolis from the semi-arid region of Brazil. This propolis showed growth inhibition of L. amazonensis promastigotes with IC 50 values ranging from 4Á96 to 36Á95 lg ml À1 , depending on the extraction solvent of the samples.…”
Section: Antiprotozoal Activitymentioning
confidence: 99%
See 1 more Smart Citation